Google Maps App Used to Enhance Students’ Speaking Performance in Asking and Giving for Information - Sari, Eny Maulita Purnama; Aini, Nurul; Efendi, Ahmad; Sholihah, Nihayatus (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Technology has proven to be a powerful instrument in enhancing students’ enthusiasm and skills in learning English, both in written and spoken forms. Teachers are encouraged to implement creative, interest-based teaching strategies, such as the use of Google Maps App and educational software, to align with students’ preferences and needs. This research investigated the effectiveness of the using Google Maps App as an interactive learning medium to enhance students’ speaking performance in asking and giving for information at Madrasah Tsanawiyah Negeri 2 East Lampung. The research employs a qualitative descriptive method. The research involves the VIIa class, using a combination of observation, test and documentation for data collection. The findings describe that the using Google Maps App App in teaching speaking can enhance students’ performance, motivation and engagement. The research also highlights the potential of using technology and internet-based learning to be an interactive learning medium. This research provides valuable insight for educators in the using technology to developing innovative teaching strategies to enhance students’ speaking performance.